CLIMATE-ADAPTIVE DRAINAGE DESIGN BASED ON RAINFALL INTENSITY–DURATION–FREQUENCY ANALYSIS AND RUNOFF SIMULATION - Nurnawaty Nurnawaty (Yayasan Nusantara Hasana Berdikari, 2024)
This study aims to develop a climate-adaptive drainage design framework through the integration of rainfall Intensity Duration Frequency (IDF) analysis and runoff simulation. Historical rainfall data from 2000–2026 were analyzed to evaluate rainfall variability, extreme rainfall characteristics, and hydrological responses under different land-use conditions. The results indicate an average annual rainfall of 3,249 mm/year with increasing variability in recent years, suggesting a growing influence of climate variability on extreme rainfall events. Frequency analysis using the Log-Pearson Type III distribution was employed to derive design rainfall and construct IDF curves. The analysis shows that rainfall intensity increases significantly with shorter storm durations and higher return periods. Runoff simulations further reveal that urbanized areas generate substantially higher peak discharges than permeable land covers due to greater surface imperviousness. These findings highlight the importance of integrating IDF-based hydraulic design, land-use management, and green infrastructure measures to improve drainage system resilience. The proposed approach provides a practical framework for enhancing urban drainage performance under changing climatic conditions.